Implementasi Pendidikan Ramah Anak Untuk Meningkatkan Keaktifan Belajar Siswa Kelas Atas Di Sd Muhammadiyah Program Khusus Kottabarat Surakarta Tahun Pelajaran 2016/2017 - Harnanto, Nanda; , Ratnasari Diah Utami, S.Pd, M.Pd (2017)
The aim of the research is to describe: 1) Implementation of child-friendly education in Special Programs Kottabarat SD Muhammadiyah Surakarta, 2) Efforts to enhance the activity of upper grade students through the implementation of child-friendly education., 3) barriers and solutions to enhance the students' learning activeness upscale .. This type of research is a qualitative research design descriptive analysis. Data collection techniques used were interviews, observation, and documentation. The validity of the data using triangulation and triangulation techniques. Data were analyzed using interactive data analysis model. The results of this study show that: 1) Implementation of friendly education of children in SD Muhammadiyah Special Program Kottabarat Surakarta apply the principle of 3P namely Provision (school menyedikan snack and lunch, menyediakaan drinking water, the infirmary, bathrooms, lockers, habituation prayer, the box P3K, cooperatives), protection (there are security guards, there are two teachers in every grade), participation (students participate in making the learning contract, making classroom rules, choose extracurricular). 2) Efforts to enhance the students' learning activeness like cooperation principals with teachers, problem-based learning, attitudes of teachers were friendly, and the use of media in learning. 3) Barriers experienced in improving students' learning activeness is students tend to feel frightened, students have felt able, students are less healthy or sick, there is a problem of home students, and students do not want to cooperate. Solutions to address these barriers with the reward, learning in a group, and a personal approach.